2018
DOI: 10.1093/mnrasl/sly236
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic spectral transition of X-ray pulsar GX 304−1 in low luminous state

Abstract: We report on the discovery of a dramatic change in the energy spectrum of the Xray pulsar GX 304−1 appearing at low luminosity. Particularly, we found that the cutoff power-law spectrum typical for accreting pulsars, including GX 304−1 at higher luminosities of L X ∼ 10 36 −10 37 erg s −1 , transformed at lower luminosity of L X ∼ 10 34 erg s −1 to a two-component spectrum peaking around 5 and 40 keV. We suggest that the observed transition corresponds to a change of the dominant mechanism responsible for the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 34 publications
6
32
0
Order By: Relevance
“…The hard component is produced by inverse Compton scattering of the photons of the soft compo-nent by the electrons in the atmosphere just outside the magnetosphere during the flares and the low luminosity states (if magnetic reconnections takes place). According to the recent findings of Tsygankov et al (2019), bulk Comptonization of the leaking matter should be negligible because of the small optical depth expected at the accretion rates occurring during the low luminosity level of A0538−66. When the accretion on the surface decreases dramatically, the soft component decreases suddenly.…”
Section: Discussionmentioning
confidence: 95%
“…The hard component is produced by inverse Compton scattering of the photons of the soft compo-nent by the electrons in the atmosphere just outside the magnetosphere during the flares and the low luminosity states (if magnetic reconnections takes place). According to the recent findings of Tsygankov et al (2019), bulk Comptonization of the leaking matter should be negligible because of the small optical depth expected at the accretion rates occurring during the low luminosity level of A0538−66. When the accretion on the surface decreases dramatically, the soft component decreases suddenly.…”
Section: Discussionmentioning
confidence: 95%
“…Motivated by recent NuSTAR observations of the transient X-ray pulsars GX 304−1 (Tsygankov et al 2019a) and A 0535+262 (Tsygankov et al 2019b), which allow the direct study of the broadband X-ray spectrum emitted by highly magnetized neutron stars at lowṀ, in this paper we consider the spectral formation in the atmosphere of a neutron star. Specifically, the NuSTAR observations were performed at luminosities of ∼10 34 erg s −1 for GX 304−1 and ∼7 × 10 34 erg s −1 for A 0535+262.…”
Section: Introductionmentioning
confidence: 99%
“…The spectra of X Persei (green points;Doroshenko et al 2012), GX 304−1 (grey points;Tsygankov et al 2019) and A 0535+262 (this work) observed at low accretion rates, along with the best-fitting models consisting of two Comptonization components (black solid lines). Separate model components (comptt in xspec) are shown with dashed lines.…”
mentioning
confidence: 99%